Pemodelan Hujan Netto Berdasarkan Tutupan Lahan untuk Analisa Debit Aliran Rendah - Avianta, Adhi Yanuar; Rispiningtati, Rispiningtati; Limantara, Lily Montarcih; Suhartanto, Ery (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2019)
This research intends to investigate the land cover change and to obtain the canopy interception in the Lesti sub-watershed, and to produce the rainfall-discharge modeling as the function of net rainfall factor. The methodology consisted of identifying the land cover based on the Normalized Difference Vegetation Index (NDVI) classification of digital satellite images Landsat TM 7 and TM 8, carrying out the field study to obtain the canopy interception used a volume balance approach. The interception rate of Lesti sub-watershed are 5 – 7 % in everage of rainfall, the net-rainfall models of Lesti sub-watershed are Pnetto= P - (-1E07P² + 0.059P +0.260) for land clasification II and Pnetto = P – (-1E07P² + 0.199P + 0.16) for land clasification III, it used as the input on the rainfall-discharge modeling of F.J. Mock, the result showed that the use of net-rainfall on the rainfall-discharge modeling of F.J. Mock increased the accuracy of generated discharge which is strongly influenced by the proportional of land classification.